80 Jahre deutsche Autobahn. Bau der Kraftwagenstraße Köln-Bonn. - Gabriel, Roland; Wirth, Wolfgang (Deutscher Verkehrs-Verl., 2009)
Die Kraftwagenstraße Köln-Bonn wurde, im Gegensatz zur AVUS, als gebührenfreie, reine Verkehrsstraße durch die öffentliche Hand finanziert. Ihr Baubeginn im Oktober 1929 markiert den Anfang des staatlichen Autobahnbaus in Deutschland, der sich nun zum 80. Male jährt, Anlass genug für eine Retrospektive über die Kraftwagenstraße, die im August 1932 eröffnet und während der gesamten Zeitspanne von 1933 bis 1945 nicht in das RAB-Netz einbezogen wurde.

The federal motorway A 555 runs from Cologne, the old hanseatic city, to Bonn, the former capital of the Federal Republic of Germany. This section of federal motorway A 555 is a road with an eventful past. Its first origins go back to pre-Christian times. In actual fact the section of the A 555 was constructed as "Kraftwagenstraße Köln-Bonn" (which can be translated directly into English as vehicles road Cologne-Bonn) from 1929 until 1932 and can be regarded as the first "German Autobahn". The 20 km long section connects two industrial regions and runs through highly urbanized areas. The route concentrates several traffic relations in one bundle on the west bank of the river Rhine. It is the only German motorway, built before the "Third Reich". The road construction started in October 1929, 80 years ago. That was the reason to write the article.
80 years ago: the first "German Autobahn".
Keywords: Verkehr; Straßenverkehr; Verkehrswegebau; Autobahn; Autobahnbau; Straßenbau; Schnellstraße; Baugeschichte; Verkehrswegefinanzierung; Verkehrsgeschichte